In Colon Epithelia, Clostridium perfringens Enterotoxin Causes Focal Leaks by Targeting Claudins Which are Apically Accessible Due to Tight Junction Derangement. (15th September 2017) - Eichner, Miriam; Augustin, Christian; Fromm, Anja; Piontek, Anna; Walther, Wolfgang; Bücker, Roland; Fromm, Michael; Krause, Gerd; Schulzke, Jörg-Dieter; Günzel, Dorothee; Piontek, Jörg
Abstract : CPE targets a subpopulation of colonocytes, thereby inducing focal barrier leaks. CPE-mediated damage is restricted by an intact tight junctional barrier. Toxicity and barrier disruption by CPE are mediated by apically dislocated nonjunctional claudins that serve as CPE receptors. Abstract: Clostridium perfringens enterotoxin (CPE) causes food poisoning and antibiotic-associated diarrhea. It uses some claudin tight junction proteins (eg, claudin-4) as receptors to form Ca 2+ -permeable pores in the membrane, damaging epithelial cells in small intestine and colon. We demonstrate that only a subpopulation of colonic enterocytes which are characterized by apical dislocation of claudins are CPE-susceptible. CPE-mediated damage was enhanced if paracellular barrier was impaired by Ca 2+ depletion, proinflammatory cytokine tumor necrosis factor α, or dedifferentiation. Microscopy, Ca 2+ monitoring, and electrophysiological data showed that CPE-mediated cytotoxicity and barrier disruption was limited by extent of CPE-binding. The latter was restricted by accessibility of non-junctional claudin molecules such as claudin-4 at apical membranes. Focal-leaks detected in HT-29/B6 colonic monolayers were verified for native tissue using colon biopsies. These mechanistic findings indicate how CPE-mediated effects may turn from self-limiting diarrhea into severe clinical manifestation such as colonic necrosis—if intestinal barrier dysfunction, eg, during inflammation facilitates claudin accessibility.